THE CLASSROOM MANAGEMENTS APPLIED BY THE ENGLISH TEACHERS BASED ON CURRICULUM 2013 - Elvira Afifah; Elfrida Elfrida; Mukhrizal Mukhrizal (Universitas Bengkulu, 2022)
The objective of this research was to investigate the classroom managements based on curriculum 2013 applied by the English teachers of SMP Negeri 9 Kota Bengkulu in the academic years 2021/2022. The subjects consisted of three English teachers that were; teacher A (Female), teacher B (Female), and teacher C (Male). This research utilized descriptive qualitative method. The data were obtained by the observation checklist and interview guideline. The results of this study displayed those three English teachers applied 10 of 10 the components of classroom management curriculum 2013, but the teachers did not apply all the features. Teacher A dominantly used 3 of 10 components there were; 1) Teacher Feedback, 2) Teacher Wardrobe and 3) Adjusting the Material with The Students’ Learning Ability, with the total of all component’s percentage 73.4%. Teacher B also dominantly used 3 of 10 components such as; 1) Teacher Voice, 2) Time Management and 3) Teacher Wardrobe, with the total of all component’s percentage 73.4%. In contrast, teacher C dominantly applied 4 of 10 components there were; 1) Teacher Feedback, 2) Students’ Talking Time, 3) Teacher Wardrobe and 4) Adjusting the Material with The Students’ Learning ability, with the total of all component’s percentage 80%. In conclusion, three English teachers applied all the components of classroom management, but they did not apply all the features.